Associations between peripheral thyroid sensitivity and all-cause and cardiovascular mortality in the US adults with metabolic syndrome - Deng, Qin; Deng, Juan; Wei, Xiaoyuan; Shen, Lu; Chen, Jing; Bi, Ke (Frontiers in Medicine, 2024)
Background The relationship between peripheral sensitivity to thyroid hormones, as indicated by the ratio of free triiodothyronine (fT3) to free thyroxine (fT4) (fT3/fT4), and the prognosis of metabolic syndrome (MetS) remains unclear. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2012. MetS was defined based on the criteria established by the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III). Kaplan–Meier survival curves, restricted cubic spline (RCS) analysis, and Cox proportional hazards models were employed to investigate the association between peripheral thyroid sensitivity and mortality outcomes among adults with MetS. Results A total of 3,101 adult participants (1,594 males and 1,507 females; median age: 52.00 years) with MetS were included in the analysis. Multivariate Cox regression analysis revealed that elevated levels of fT4 were positively associated with increased risks of both all-cause and cardiovascular mortality in the MetS population [adjustedhazard ratio (aHR): 2.74, 95% confidence interval (CI): 1.94–3.87, p < 0.001 for all-cause mortality; aHR: 3.93, 95% CI: 2.07–7.45, p < 0.001 for cardiovascular mortality]. Conversely, higher levels of fT3 and the fT3/fT4 ratio were found to be protective factors, reducing the mortality risk in the MetS population (fT3: aHR: 0.76, 95% CI: 0.57–0.99, p = 0.046 for all-cause mortality; fT3/fT4 ratio: aHR: 0.75, 95% CI: 0.67–0.85, p < 0.001 for all-cause mortality; aHR: 0.66, 95% CI: 0.52–0.83, p < 0.001 for cardiovascular mortality). The fT3/fT4 ratio exhibited a nonlinear association with all-cause mortality, but a linear and inverse association with cardiovascular mortality. Conclusion The findings of this study suggest that higher peripheral thyroid sensitivity, as indicated by the fT3/fT4 ratio, may be associated with reduced mortality risks among adults with MetS. Further research is warranted to validate these associations.